A Schulman posts increased sales as earnings fall in 1Q fiscal 2016. Issue 3 (March 2016) - Unknown
Abstract : For its fiscal 2016 first quarter ended 30 November 2015, Akron-based A. Schulman, Inc posted net sales of US$649.2 million, an increase of 5.6% compared with $615.1 million in the same quarter a year earlier. Foreign currency translation negatively impacted the total by $62 million, or 10% of sales. Net sales from the acquired Citadel Plastics business contributed $111.1 million of revenue during the quarter. Excluding the acquisition and currency effects, net sales declined by 2.4% as the company experienced lower volumes in its US and Canada (USCAN) segment's commodity product and service offerings.